"No! I Can't!": Noise and silence as everyday resistance at a Chinese suburban middle school. (March 2022) - Zhang, Min
Student resistance is one of the central themes in the study of schooling and inequality. This article used sound as a means of inquiry to investigate how China's suburban teenagers—a segment largely overlooked in prior scholarly writing—resist the school values amid the exaltation of success and widening stratification in contemporary Chinese society. Drawing on fieldwork in a suburban middle school in Northwest China, I demonstrated that students utilize a wide range of sound acts—burlesqued shouts, subdued murmurs, and sometimes pervasive silence—to resist educators' moralized lectures on the seriousness of schoolwork and the prospects of education success. Lodged in the liminal space within China's socioeconomic and spatial hierarchy, suburban youths expressed their disbelief and disillusion—both in and through sound—in an environment that offers few avenues for social mobility.